Envisioning grassroots science: DIY biology in Canada, Britain, and Germany - Anna Verena Eireiner (PLoS ONE, 2025)
This study employs the conceptual lens of sociotechnical imaginaries to examine how DIY biology is envisioned in Canada, Great Britain, and Germany. DIY biology, an extra-institutional movement, aspires to democratize biology by making research infrastructures accessible, fostering open-source knowledge, and challenging the expert-public divide. Based primarily on 23 in-depth interviews with practitioners from three countries, complemented by insights from a global online survey of 152 DIY biologists and additional perspectives from policymakers, this research highlights how country-specific sociopolitical contexts shape the local identities and practices of a global movement. The findings reveal country-specific differences in the ways DIY biology is envisioned and materialized. Canadian DIY biologists often adopt entrepreneurial narratives akin to “garage start-ups,” critiquing the high cost of higher education and the rigidity of traditional research institutions. German practitioners, emphasizing sustainability and responsibility, critique capitalism while aligning their DIY efforts with environmental activism. In Great Britain, DIY biologists often focus on collective benefits, thereby highlighting global equity and collaboration. Despite their differences, DIY biologists across all three countries share aspirations to foster inclusivity, intellectual freedom, and socially relevant research, while dealing with challenges like a lack of funding to conduct their experiments and maintain laboratory spaces. By exploring how grassroots science movements navigate challenges and reimagine scientific practices, this study contributes to scholarship in Science and Technology Studies (STS). It provides an empirically rich, comparative perspective on how a global movement is envisioned within different sociopolitical contexts across countries. This research underscores the potential of DIY biology to democratize science but also calls for critical reflection on its systemic challenges, offering actionable insights for cultivating sustainable, community-driven scientific practices.